197k views
22 votes
Given f (x) = 2^x – 1 and g (x) = 3x – 4, find (f + g)(2).

Given f (x) = 2^x – 1 and g (x) = 3x – 4, find (f + g)(2).-example-1
User Uooq
by
5.6k points

1 Answer

6 votes

Answer:

(f+g)(2) = 5

Explanation:

(f+g)(2) means

f(2) + g(2)

Add the functions and substitute in 2 for the x.

2^2 - 1 + 3(2) - 4

Simplify.

4 - 1 + 6 - 4

3 + 6 - 4

9 - 4

5

User Federico Ojeda
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.